FAKTOR-FAKTOR YANG MEMENGARUHI KEPUASAN KERJA KARYAWAN KLINIK KESEHATAN DI KOTA BEKASI - Amanda Setiorini; Wiwik Rachmarwi (Jurnal Ekonomi dan Industri, 2020)
This study aims to find out whether factors such as compensation, job certainty, career path, communication, relationships with superiors, and work-life balance affect job satisfaction in three health clinics. In this research is descriptive quantitative. The results show that compensation, job certainty, communication, and work-life balance affect job satisfaction. Data processing is performed using multiple regression methods